Sociodemographic and metabolic profile of term and preterm adolescents (Research, Society and Development, 2022)
This study aims to identify and describe the sociodemographic, anthropometric, pressure, glycemic and lipid profile of term and preterm adolescents. Study of quantitative approach, cross-sectional design, associated with analysis of primary and secondary data. The sampling consisted of 150 adolescents between 10 and 19 years of age, born at term, and 50 adolescents born prematurely. Interviews and physical evaluation of adolescents were conducted (blood pressure measurement, anthropometric measurement, abdominal circumference and blood collection by capillary puncture for glucose, total cholesterol and triglyceride scans). For statistical analysis, the Chi-square test for independence (α=0.05) was used. Most adolescents were between 10 and 13 years old and self-reported as white. The parents had 7 to 12 years of study and had employment. The healthiest food intake was detected among premature adolescents, with breastfeeding above six months for the majority in both groups. Physical activities were identified with inadequate frequency. The majority are eutrophic individuals, however, 34% of full-term and 30% of preterm infants were overweight or obese. There were no differences between anthropometric, blood pressure and glycemic profiles between the groups.